Structuring light to improve laser brightness - Scholes, Stirling (My University, 2020)
The ability to create ‘structured’ light with precisely controlled amplitude, phase and polarisation profiles has led to many new applications of light, including high-energy lasers in the defence sector. Laser systems which simultaneously produce high energy yet low divergence (‘bright’) beams have remained elusive. In particular, solid-state lasers suffer deleterious thermally-induced optical and stress effects, limiting the total energy which can be added to the system. Additionally, performing safe and accurate characterisations of high energy beams has proved challenging. Here, the theoretical and experimental tools of structured light are applied to develop brighter laser systems and characterise them. Specifically, this work derives and experimentally demonstrates a lossless phase-only reshaping method which significantly enhances the brightness of abeam for a given power by reducing its divergence. Further, this work shows that using abeam with an annular intensity profile mitigates the deleterious thermal effects in solid state lasers, raising the energy limit. When used together, these approaches can enhance brightness by four orders of magnitude. A low energy physical simulator for high energy laser sources, built around a Digital Micro-mirror Device is demonstrated, allowing fort he safe characterisation of high-energy sources at lower cost and complexity
This dissertation is submitted for the degree of Master of Science, School of Physics, University of the Witwatersrand, 2020